2012
DOI: 10.1159/000339347
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Metabolic Responses to Methionine-Restricted and Methionine-Restricted, Cysteine-Supplemented Diets in Fischer 344 Rat Inguinal Adipose Tissue, Liver and Quadriceps Muscle

Abstract: Background/Aims: Methionine restriction (MR) is a dietary intervention that increases lifespan, reduces adiposity and improves insulin sensitivity. These effects are reversed by supplementation of the MR diet with cysteine (MRC). Genomic and metabolomic studies were conducted to identify potential mechanisms by which MR induces favorable metabolic effects, and that are reversed by cysteine supplementation. Methods: Gene expression was examined by microarray analysis and TaqMan quantitative PCR. Levels of selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
104
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(117 citation statements)
references
References 120 publications
12
104
1
Order By: Relevance
“…58 In this line, a recent metabolomic and genomic MetR study found changes in the expression of a large number of genes and proteins that led the authors to conclude that MetR increases lipid metabolism in adipose tissue and muscle, whereas it decreases lipid synthesis in the liver. 59 Therefore, these changes in lipid metabolism seem to be involved in the strong decrease in adiposity and increased insulin sensitivity observed in isocaloric restriction of dietary methionine.…”
Section: Effect On Longevitymentioning
confidence: 99%
See 3 more Smart Citations
“…58 In this line, a recent metabolomic and genomic MetR study found changes in the expression of a large number of genes and proteins that led the authors to conclude that MetR increases lipid metabolism in adipose tissue and muscle, whereas it decreases lipid synthesis in the liver. 59 Therefore, these changes in lipid metabolism seem to be involved in the strong decrease in adiposity and increased insulin sensitivity observed in isocaloric restriction of dietary methionine.…”
Section: Effect On Longevitymentioning
confidence: 99%
“…Interestingly, adding cysteine to the MetR diet reverses most of the studied beneficial changes on adiposity and insulin resistance 60 and increases the transcription of various genes associated with inflammation and carcinogenesis. 59 Therefore, the beneficial changes of MetR diet have been attributed to the decrease of cysteine in serum 60 or liver 59 observed in animals subjected to MetR. On the other hand, excessive intake of dietary methionine is toxic.…”
Section: Effect On Longevitymentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidence suggests that improved mitochondrial function and decrease in mitochondrial reactive oxygen species (ROS) generation might be critical factors that contribute to the effects observed (Perrone et al, 2012(Perrone et al, , 2013. Mitochondria are the major intracellular organelles responsible for biological oxidation in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%